The oral manifestations of syphilitic disease: a case report - Kaitlyn L. Streight; Ronald M. Paranal; Daniel M. Musher (Journal of Medical Case Reports, 2019)
Abstract Background Syphilis is a sexually transmitted bacterial infection of the spirochete, Treponema pallidum. While primary syphilis often involves genitalia, oral manifestations are observed in a subset of patients. These lesions are often associated with submandibular and cervical lymphadenopathy. This is a case report of a primary syphilitic lesion located on the hard palate of the oral cavity, with only a very few cases described previously. Case presentation We describe a rare case of syphilis in a 59-year-old African American man presenting with subjective fevers, chills, marked submental lymphadenopathy, a diffuse skin rash, and an ulcer of the hard palate. Conclusions This case report demonstrates the importance of maintaining a high index of suspicion for syphilitic infection when a patient presents with nonspecific symptoms, a diffuse rash, and an oral lesion.